Hubungan Pengetahuan dengan Sikap Ibu tentang Pemilihan Pijat Bayi yang Dilakukan oleh Bidan dan Dukun di Kelurahan Pegirian Kecamatan Semampir Surabaya - Putri, Ardelia Savinka Anandrian; Sari, Gadis Meinar; Ningrum, Astika Gita; Puspitasari, Dwiyanti (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2024)
Infant mortality could have been prevented if the baby's condition was healthy and of high quality. One effort to improve the health and developmental stimulation of infants that can be undertaken by the community is by providing stimulation through infant massage. The aim of this research was to determine the relationship between knowledge and the attitude of mothers regarding the selection of infant massage performed by midwives and traditional birth attendants in the Pegirian Subdistrict of Surabaya. The research method used was quantitative analytical observational with a cross-sectional approach. The sample size was 63 respondents using consecutive sampling technique. The research instrument used a questionnaire and was analyzed using the chi-square test. The majority of respondents had good knowledge, with 40 respondents (63.49%), and the majority of respondents chose infant massage by midwives, with 33 respondents (52.38%). The chi-square test results showed a relationship between knowledge and the attitude of mothers regarding the selection of infant massage by midwives and traditional birth attendants (p<0,01). There is a relationship between knowledge and the attitude of mothers regarding the selection of infant massage performed by midwives and traditional birth attendants in the Pegirian Subdistrict of Semampir District, Surabaya City.